A theoretical basis for public sector accrual accounting research: current state and perspectives. Issue 8 (17th November 2019) - Bergmann, Andreas; Fuchs, Sandro; Schuler, Christoph
ABSTRACT: Public sector or government accounting has been the subject of many research endeavors. However, scholars have repeatedly criticized the lack of a consistent and well-defined theoretical basis for international research. So far, most researchers have drawn from various streams of theoretical perspectives with often unsatisfactory results. The goal of this paper is to put forward the International Public Sector Accounting Standards Board's (IPSASB) Conceptual Framework as a point of reference for establishing a better-fitting theoretical basis for public sector accrual accounting research. IMPACT: This paper aims at stimulating the wider scientific debate on public sector accrual accounting research, building on the recent discussion about the lack of a solid theoretical basis for this research stream. The ever-increasing global diffusion of accrual accounting, and the subsequent increased implementation of International Public Sector Accounting Standards (IPSASs) has directed more attention to the broader political and social implications of accrual accounting. These developments are of practical relevance, since the evaluation of public sector accounting reform projects often faces difficulties, due to the lack of an appropriate theoretical basis.